Peripheral plasma progesterone concentration in Zebu (Bos indicus) cows during pregnancy - Mukasa-Mugerwa, E.; Tegegne, Azage (EDP Sciences, 1989)
A study undertaken to determine the progesterone concentration in the peripheral plasma of pregnant Ethiopian Zebu cows using the ELISA technique.